Citogenética y cito química de pacientes con leucemia en dos hospitales neotropicales - Solís, María Virginia; Alvarado, María de los Angeles; Ruiz, Edward; Carrillo, Juan Manuel; Navarrete, Martha; Sánchez, German; Jiménez, Elías (Revista de Biología Tropical, 2000)
A cytogenetic andlor cytochemical study was perforrned in 166 individuals with leukemia or related disorders, in two major Costa Rican hospitals. In thosepatJ.entstreated at an adult’s hospital (14 years oId and over),aéute leukemias represented 66% of aH cases. In that hospital the mostfrequent types of disorde , rs were, in decreasing order: ANLL (>Ml), ALL, CML(aÍl of them showed the Ph chromosome) and MDS. Inthe cases from a childréns’hospital «14 years(jld) acute leukemias were98%. Amongthem the o